Defamation: a study on the trend of awarding damages in defamation cases in Malaysia / Syazwani Soaib ...[et al.] - Soaib, Syazwani; Mahadi, Siti Zulaikha; Ishak, Nur Hidayah; Abd Aziz, Nurrul Naema; Shafaai, Nur Aiman Shazwin (2010)
The cases pertaining to the law of defamation is said to have grown tremendously according to years. The aim of this research is to study whether the amount of damages granted by the court can be regarded as substantial or reasonable. Also, the study will look on the factors which the court used in deciding cases regarding the law of defamation. The few countries that have been taken into consideration in this study are; Malaysia, Australia, United Kingdom, the United States and New Zealand. The literature review (chapter 2) will provide an overview of the law of defamation. This chapter stressed on the definition, elements and also defences available in the law itself. This is done by reviewing several sources such as law reference books, newspaper reports, articles and journals. The most significant chapter in this study, which is chapter 3 covers on the trend of awarding defamation, will try to determine the amount of damages granted by the court and whether the award is considered as substantial or reasonable. A comparison has been made in Chapter 4 of the report. This chapter clearly tells us on the factors and also the amount of damages granted by the courts in other countries. The last chapter is the findings and recommendations of the report made. In this chapter, an interviewee who is specialized in the field of defamation has been interviewed. Her feedbacks have been recorded. The central argument of this study will discuss on whether the amount of damages granted by the court is regarded as substantial or reasonable.